Edukasi Pencegahan dan Skrining Risiko Penyakit Kardiovaskular pada Peserta Prolanis di Puskesmas Limboto - Ibrahim Suleman; Suardi (GOTAVA, 2026)
Cardiovascular disease is a leading cause of mortality and is associated with risk factors such as hypertension, diabetes mellitus, obesity, smoking, physical inactivity, and unhealthy dietary patterns. This community service activity aimed to improve participants’ knowledge of cardiovascular disease prevention, estimate 10-year cardiovascular risk, and provide risk-based counseling. The activity was conducted on June 7, 2026, at Limboto Community Health Center, Gorontalo Regency, involving 66 purposively recruited participants enrolled in the Chronic Disease Management Program (Prolanis). Activities included a pretest, interactive health education, blood pressure and anthropometric measurements, risk-factor interviews, cardiovascular risk estimation using the 2007 WHO/ISH Non-Laboratory Risk Prediction Chart for South-East Asia Region B, individual counseling, and an immediate posttest. The proportion of participants with good knowledge increased descriptively from 13 (19.7%) before education to 48 (72.7%) afterward. Screening results showed that 22 participants (33.3%) were at low risk, 18 (27.3%) at moderate risk, 14 (21.2%) at moderately high risk, 9 (13.6%) at high risk, and 3 (4.6%) at very high risk. Overall, 26 participants (39.4%) were categorized as having moderately high to very high risk and received counseling and priority follow-up recommendations. The activity identified participants requiring more intensive monitoring and showed a descriptive improvement in knowledge. However, causality cannot be inferred because the evaluation used a pretest–posttest design without a comparison group and an immediate posttest. Health education, cardiovascular risk screening, counseling, and monitoring should be integrated into routine Prolanis activities.